Black-White Achievement Gap: Role of Race, School Urbanity, and Parental Education - Assari, Shervin (Pediatric Health Med Ther, 2021)
BACKGROUND: Recent research on Marginalization-related Diminished Returns (MDRs) has documented weaker boosting effects of parental educational attainment on educational outcomes of Black than White students. Such MDRs of parental education seem to contribute to the Black-White achievement gap. Given that Blacks are more likely than Whites to attend urban schools, there is a need to study if these MDRs can be replicated at both urban and suburban schools. AIM: To test the contribution of diminished returns of parental educational attainment on the Black-White achievement gap in urban and suburban American high schools. METHODS: A cross-sectional study that used baseline Education Longitudinal Study (ELS-2002) data, a nationally representative study of 10th grade adolescents in the United States. This study analyzed 8315 youths who were either non-Hispanic White (n = 6539, 78.6%) or non-Hispanic Black (n = 1776, 21.4%) who were attending either suburban (n = 5188, 62.4%) or urban (n = 3127, 37.6%) schools. The outcome was standard math and reading grades. The independent variable was parental educational attainment. Gender, parental marital status, and school characteristics (% free lunch and relationship quality with the teacher) were the confounders. Race/ethnicity was the effect of modifier. School urbanity was the strata. Linear regression was used for data analysis. RESULTS: In urban and suburban schools, higher parental educational attainment was associated with higher math and reading test scores. In urban and suburban schools, Black students had considerably lower reading and math scores than White students. At urban but not suburban schools, significant interactions were found between race (Non-Hispanic Black) and parental education attainment (years of schooling) on reading and math scores, suggested that the protective effect of parental education on students’ reading and math scores (ie school achievement) is smaller for Non-Hispanic Black relative to Non-Hispanic White youth only in urban but not sub-urban schools. CONCLUSION: Diminished returns of parental education (MDRs) contribute to the racial achievement gap in urban but not suburban American high schools. This result is important given Black students are more likely to attend urban schools than White students. As MDRs are not universal and depend on context, future research should study contextual characteristics of urban schools that contribute to MDRs.